Pengembangan Media Akuntansi Digital Berbasis Full Costing Sebagai Dasar Penetapan Harga Jual Pada UMKM Kripik Pisang Krinana - Setiawan, Muchamad Indra; Pratama, Devangga Putra Adhitya; Widjatmiko, Andrik Gastri (Program Studi Pendidikan Akuntansi Fakultas Ekonomika dan Bisnis Universitas Negeri Surabaya, 2025)
Technological advances in the creative business of micro, small, and medium enterprises (MSMEs) continue to develop, especially in digital accounting calculations. This study aims to develop a full costing-based calculation media to calculate production costs as a basis for determining selling prices in the Krinana Banana Chips MSME. This digital accounting media is designed in a full costing-based excel program to make it easier for business actors to calculate production costs and selling prices that can be accessed anytime, anywhere. This researcher uses the Research and Development (R&D) method with the ADDIE model which includes five stages: Analysis, Design, Development, Implementation, and Evaluation. Data collection techniques include tests, observations, interviews. Data analysis techniques use calculation and media feasibility analysis. The results of expert validation show a very high level of feasibility, namely 94.22% from calculation experts and 92.22% from media experts who stated that this media is valid in terms of method, construction, language, content, instruction, technical quality. The results of responses by business actors show a very effective category. The results of knowledge tests by business actors show practicality. Thus, this full costing-based excel calculation media can be a solution to increase the effectiveness of selling price calculations.